2012
DOI: 10.1177/0023830912443942
|View full text |Cite
|
Sign up to set email alerts
|

Intonation as an Encoder of Speaker Certainty: Information and Confirmation Yes-No Questions in Catalan

Abstract: Recent studies in the field of intonational phonology have shown that information-seeking questions can be distinguished from confirmation-seeking questions by prosodic means in a variety of languages (Armstrong, 2010, for Puerto Rican Spanish; Grice & Savino, 1997, for Bari Italian; Kügler, 2003, for Leipzig German; Mata & Santos, 2010, for European Portuguese; Vanrell, Mascaró, Prieto, & Torres-Tamarit, 2010, for Catalan). However, all these studies have relied on production experiments and little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 35 publications
0
39
2
Order By: Relevance
“…The authors also found that Bari Italian speakers use a L+H* accent in which the peak is higher than the peak of the same pitch accent observed in unbiased contexts to signal that the speaker believes the content of the proposition to be false (Savino & Grice, 2007). Vanrell et al (2013) also showed that a difference in pitch scaling could signal speaker commitment in Majorcan Catalan. Specifically, they found that the scaling of the leading H tone of the H+L* pitch accent indicates the contrast between information-seeking questions and confirmation-seeking questions.…”
Section: Intonational Encoding Of Speaker Commitment Across Languagesmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors also found that Bari Italian speakers use a L+H* accent in which the peak is higher than the peak of the same pitch accent observed in unbiased contexts to signal that the speaker believes the content of the proposition to be false (Savino & Grice, 2007). Vanrell et al (2013) also showed that a difference in pitch scaling could signal speaker commitment in Majorcan Catalan. Specifically, they found that the scaling of the leading H tone of the H+L* pitch accent indicates the contrast between information-seeking questions and confirmation-seeking questions.…”
Section: Intonational Encoding Of Speaker Commitment Across Languagesmentioning
confidence: 93%
“…When the information is new (i.e., unknown to the speaker at the time of the asking of the question) so that the speaker has no particular bias with respect to his/her interlocutor's answer, questions have been mainly referred to in the literature as 'queries' (e.g., Carletta et al, 1997;Grice & Savino, 1997;Savino & Grice, 2011) or information-seeking questions (e.g., Armstrong, 2010;Vanrell et al, 2013). On the other hand, when the speaker refers to previously mentioned information and when he/she is biased towards the expected answer, questions have been mainly referred to as 'checks' or 'confirmation seeking-questions' for positive bias (i.e., the speaker is asking for the confirmation of shared information) or 'objects' for negative bias (i.e., the speaker is challenging what has been said; Savino & Grice, 2011;Vanrell et al, 2013). Here, we use the terms unbiased questions for 'queries' or 'information-seeking questions' and biased questions for questions such as 'checks' or 'confirmation seeking questions'.…”
Section: Intonational Encoding Of Speaker Commitment Across Languagesmentioning
confidence: 99%
“…Unlike in EP, in Majorcan Catalan phonetic differences in peak height in the H+L* nuclear fall have been reported to be systematically related to the distinction between information-seeking and confirmation-seeking yes-no questions Vanrell, 2011;Vanrell et al, 2012). While both types of questions are characterized by a falling nuclear pitch accent H+L*, the information-seeking question has a higher (upstepped) H tone (Figure 8, left panel) and the confirmation-seeking question a lower (non-upstepped) H tone (Figure 8, right panel).…”
Section: Peak Height In Majorcan Catalan Nuclear Fallsmentioning
confidence: 99%
“…Our results thus provide some confirmation to claims made in previous work (e.g., Payrató, 2002;Prieto & Rigau, 2007) in relation to the effects of the factor cost, although we did not find that the rising pattern was used consistently in all situations that involved a high cost. The tendency to use falling interrogative patterns in low-cost situations could be related to the fact that these falling patterns have been associated with a higher degree of certainty/confidence on the part of the speaker regarding the potential for the interlocutor to accept the proposition of the question (Vanrell, Mascaró, Torres-Tamarit & Prieto, 2013). In the case of low-cost yes-no questions, there is a higher chance that hearers will accept the proposition, and thus speakers tend to use falling question intonation more often.…”
Section: Discussionmentioning
confidence: 99%